(untitled) (Medicine Today, 2021)
Introduction: An ectopic pregnancy is an emergency condition worldwide now a days which defined as a pregnancy that progresses after implantation of the blastocyst anywhere other than the endometrium lining the uterine cavity. Objective: In this study our main goal is to identify clinical outcome and operative situation in patients. Materials and Methods: This descriptive study was performed from January 2015 to December, 2018 at tertiary medical College & Hospital. During the study 200 patients were evaluated and data was extracted from socio-demographic, menstrual, obstetric and clinical history of the patients. Results: most of the patients belong to 30 years (19.7%) age group and history of pelvic infection (26.26%), induced abortion (17.4%), previous MR (16.26%) and sub fertility (11.25%) were common risk factor in ectopic pregnancy found in the study. Also majority of the patients faced laparotomy followed by right sided salphinogectomy (40.40%) which was the most common operation. Conclusion: quick diagnosis, classifying of risk factors and timely intervention in the form of surgical treatment is necessary for reduction mortality rate in ectopic pregnancy. Medicine Today 2021 Vol.33(2): 160-164